ANALISIS TEKNIS PERSYARATAN PENEMPATAN PERALATAN DAN MOBILITAS MASYARAKAT TERHADAP PANCARAN LOCALIZER MENGGUNAKAN DIAGRAM FISHBONE DI BANDAR UDARA ADI SOEMARMO SOLO - Athfal Aldiefa; Sabdo Purnomo; Dian Anggraini (Politeknik Penerbangan Indonesia Curug, 2019)
Airport is a providers of air transportation services are required to provide service, safety and flight safety at all times. Safety, security and comford are tools of the flight in the word. Therefore the need to identify potential hazard and then determine hazard factors and provide options as a sustainable system. equipment placement, facility area the localizer at Adi Soemarmo Solo airport is outside the airport area and blocked by the highway. Community mobility is also quite high because of the road the highway is one of the accesses to adi soemarmo solo airport. it is hoped that this analysis can be useful for Adi Soemarmo Solo airport and AIRNAV Indonesia , Solo, branch as a form of advice to get it utilized for security services and flihgt navigation for supporting flight safety in Indonesia.